Solifenacin in Multiple Sclerosis Patients with Overactive Bladder: A Prospective Study - Farida van Rey; John Heesakkers (Advances in Urology)
Objective. To assess the efficacy and the effect on Qol of solifenacin for the treatment of OAB in MS patients. Patients and Methods. Thirty MS patients suffering from OAB were treated with solifenacin 5/10 mg for 8 weeks. The first 4 weeks patients received solifenacin 5 mg. At week 4 patients could request a dose increase to 10 mg. The efficacy was evaluated at 8 weeks. Results. After 4 weeks of treatment, 28 patients reported acceptable or no side effects. 17 continued the study with the 10 mg dosage, and 11 stayed on 5 mg solifenacin. Two patients withdrew from the study due to side effects. Solifenacin 5/10 mg for 8 weeks resulted in a significant decrease in number of micturitions and number of pads used per day compared to baseline. Also the severity of urgency prior to voiding decreased significantly, and an increase was seen in the volume per void. Twenty out of 30 patients chose to continue solifenacin therapy after termination of the study. The majority of patients reported global QoL improvement. Conclusions. Solifenacin is effective in the treatment of MS patients with OAB symptoms. This is the first study with solifenacin in a specific neurogenic patient group with a neurogenic disease-specific QoL outcome measure (MS-QoL 54).